Does Institutional Quality Matter in the Relationship Between Competition and Bank Stability? Evidence from Asia - Muizzuddin Muizzuddin; Eduardus Tandelilin; Mamduh Mahmadah Hanafi; Bowo Setiyono (Faculty of Economics and Business, Universitas Gadjah Mada, 2021)
Introduction/Main Objectives: This study aims to investigate whether competition impacts bank stability. Furthermore, the study also analyzes the role of institutional quality in a country, such as voice and accountability, political stability, government effectiveness, regulatory quality, the rule of law, and control of corruption, forming the effect of competition on bank stability. Background Problem: Analysis of the relationship between competition and bank stability has been at the center of academic and policy debate. However, the theoretical and empirical research has not concluded whether bank competition leads to more or fewer stable banks. Novelty: We consider institutional quality's role in mitigating the negative impact of competition on bank stability, which has mainly been under-elaborated in prior studies, particularly in using measures from The World Bank’s Worldwide Governance Indicators, which measure how the institutions of each country influence bankers’ and the people's behavior, as part of the cultural system. Research Methods: Using a sample of 427 Asian commercial banks from 2011 to 2019, we employ the generalized method of moments (GMM) estimator and consider loan growth and the cost to income ratio as instrumental variables. Findings/Results: We find robust evidence that competition erodes bank stability. Besides, better institutional quality, especially government effectiveness, regulatory quality, the rule of law, and corruption control in each country are important aspects that promote bank stability and mitigate the negative impact of competition on bank stability. Conclusion: Competition has a negative impact on bank stability. Meanwhile, the quality of institutions can both promote bank stability and mitigate this negative relationship.